2013
DOI: 10.1080/00380768.2012.730476
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of Japanese pig farming using low-protein diet supplemented with amino acids

Abstract: Livestock production is indicated to be one of the major emitters of greenhouse gases (GHG), particularly methane (CH 4 ) and nitrous oxide (N 2 O), around the globe, and the reduction of these emissions is an important goal. GHG emissions as well as other environmental impacts of two pig (Sus scrofa domesticus) farming systems, one using conventional diets (CNV) and the other using low-protein diets supplemented with crystalline amino acids (LOW), were therefore evaluated by comparative life cycle assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 29 publications
2
26
1
Order By: Relevance
“…Feed input efficiency in livestock systems can also be increased. For example, pork from pigs fed diets supplemented with amino acids required less feed and emitted 5% fewer GHGs and had 28% lower eutrophication potential than pork from pigs fed unsupplemented diets (Ogino et al 2013). Similar benefits have also been found in poultry, beef, and dairy systems (Robertson and Vitousek 2009).…”
Section: Environmental Impacts Of Agricultural Input Efficiencymentioning
confidence: 82%
“…Feed input efficiency in livestock systems can also be increased. For example, pork from pigs fed diets supplemented with amino acids required less feed and emitted 5% fewer GHGs and had 28% lower eutrophication potential than pork from pigs fed unsupplemented diets (Ogino et al 2013). Similar benefits have also been found in poultry, beef, and dairy systems (Robertson and Vitousek 2009).…”
Section: Environmental Impacts Of Agricultural Input Efficiencymentioning
confidence: 82%
“…Global warming . v.76, n.2, p.102-111, March/April 2019 potential associated with IAA production is higher per kg of product than for grain or soybean meal production (Ogino et al, 2013). The benefits of the IAA addition related to the reduction of nitrogen excretion during housing and, consequently, lower nitrogen gaseous emissions, might compensate for the higher impact of low CP diet.…”
Section: Global Warming Potential and Cumulative Energy Demandmentioning
confidence: 99%
“…Nitrogen and phosphorus contribute to the eutrophication process and nitrogen contributes to the acidification process by ammonia emissions (Guinée et al, 2002). For this reason, most research evaluating the effect on dietary CP reduction for pigs reported a reduction on AP and EP with low CP diets (Ogino et al, 2013;Garcia-Launay et al, 2014;Mackenzie et al, 2016;Kebreab et al, 2016). In the above-mentioned researches, data were not evaluated statistically and the effect of between-animal variability was also not taken into account.…”
Section: Potential Of Acidification and Eutrophicationmentioning
confidence: 99%
“…In the study of OGINO et al (2013) AP and EP per kg of pig produced were reduced by about 2 and 9%, respectively, for each percentage unit of CP content reduction. Likewise, GARCIA-LAUNAY et al (2014) reported that the reduction of dietary protein content lessened the AP impact by about 5% and the EP impact by about 3%, for each percentage unit of CP content.…”
Section: Nutrition and Acidification And Eutrophication Potential Of mentioning
confidence: 99%
“…Evaluating the environmental impacts of pig production with a conventional or a low CP diet in a Japanese system, OGINO et al (2013) reported that the low CP diets resulted in a lower GWP (6%) per pig produced than conventional diets. This represented a 2% reduction in the GWP for each percentage unit of CP content.…”
Section: Nutrition and Global Warming Potentialmentioning
confidence: 99%